An unusual endobronchial lesion: expanding the differential diagnosis. Issue 5 (19th April 2019) - Leonard, Rachel; Schultz, Charles; Hadique, Sarah
Abstract : Synovial sarcoma is a rare tumour, accounting for approximately 2.5–10% of all soft tissue sarcomas. In the thorax, it most often presents as a large, homogenous mass and, most commonly, is the result of extrathoracic tumour metastasis. Here, we report a case of a 73‐year‐old male who presented to the hospital after a motor vehicle collision. Chest computed tomography demonstrated a 2.0 × 2.4 cm left lower lobe pulmonary nodule with endobronchial extension and a 2.5 × 2.1 cm right‐sided kidney mass. He was eventually diagnosed with monophasic synovial sarcoma. To date, only seven other cases of primary pulmonary synovial sarcoma with endobronchial extension have been reported. A review of the cases and literature is discussed. Abstract : Here, we report a case of a 73‐year‐old male who presented to the hospital after a motor vehicle collision, with incidentally found pulmonary nodule and kidney mass. He was eventually diagnosed with high‐grade synovial sarcoma, one of only seven cases to date of primary endobronchial synovial sarcoma that have been reported. A review of the cases and literature is carried out.